2010
DOI: 10.1094/mpmi-23-9-1217
|View full text |Cite
|
Sign up to set email alerts
|

BAX INHIBITOR-1 Is Required for Full Susceptibility of Barley to Powdery Mildew

Abstract: BAX INHIBITOR-1 (BI-1) is one of the few proteins known to have cross-kingdom conserved functions in negative control of programmed cell death. Additionally, barley BI-1 (HvBI-1) suppresses defense responses and basal resistance to the powdery mildew fungus Blumeria graminis f. sp. hordei and enhances resistance to cell death-provoking fungi when overexpressed in barley. Downregulation of HvBI-1 by transient-induced gene silencing or virus-induced gene silencing limited susceptibility to B. graminis f. sp. hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 61 publications
0
60
1
3
Order By: Relevance
“…This behavior contrasted to negative mid-parent heterotic effects of the same hybrid population for susceptibility to leaf rust and Septoria tritici blotch. Generally, TIGS was found to be a reliable tool of gene discovery because we and others could reproduce TIGS-triggered changes in Bgh interaction phenotypes in stable transgenic RNAi plants or mutants of barley or Arabidopsis [23,30,34,[54][55][56]. The TIGS results from the host screening with Bgh were combined with transcript profiling, association genetic, QTL co-localization as well as CNV results leading to a meta-dataset to which we assigned CE scores ranging from zero to 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior contrasted to negative mid-parent heterotic effects of the same hybrid population for susceptibility to leaf rust and Septoria tritici blotch. Generally, TIGS was found to be a reliable tool of gene discovery because we and others could reproduce TIGS-triggered changes in Bgh interaction phenotypes in stable transgenic RNAi plants or mutants of barley or Arabidopsis [23,30,34,[54][55][56]. The TIGS results from the host screening with Bgh were combined with transcript profiling, association genetic, QTL co-localization as well as CNV results leading to a meta-dataset to which we assigned CE scores ranging from zero to 6.…”
Section: Discussionmentioning
confidence: 99%
“…It remains open if some of these susceptibility-related genes are also co-opted by Bgh to facilitate fungal accommodation. To address the alternative possibility that certain constructs caused cell damage or death, which would also have prevented haustoria formation, by silencing genes with essential housekeeping function we tested all resistance-enhancing constructs in a cell-death assay, as reported [33][34][35]. This assay is based on reduced anthocyanin accumulation after induction of the pathway by transiently expressed C1 and b-Peru transcription factors with or without co-bombarded TIGS constructs.…”
Section: Qr Screening By Tigsmentioning
confidence: 99%
“…Transformation of 7-d-old barley leaves was performed as described earlier (Douchkov et al, 2005;Eichmann et al, 2010) with the PDS-1000/He System (Bio-Rad Laboratories) plant transformation gun with hepta-adapter. In all overexpression experiments, each shot delivered 1-mm gold particles (25 mg/mL) coated with 7 mg of the respective expression construct pGY-1-RFP-MAGAP1, pGY-1-RFP-MAGAP1 R185G, pGY-1-RFP-MAGAP1 DCter, pGY-1-RFP-MAGAP1 Cter, or the empty vector control pGY-1-RFP, and 3.5 mg of the reporter plasmid pGY-1-GFP.…”
Section: Transient Overexpression and Tigsmentioning
confidence: 99%
“…Microscopy evaluation of B. graminis f. sp hordei penetration success was performed according to Eichmann et al (2010).…”
Section: Transient Overexpression and Tigsmentioning
confidence: 99%
“…27 On the other hand, overexpression of barley BI-1 resulted in partial resistance to cell death induced by necrotrophic fungal pathogen Fusarium graminearum, which activates PCD of host plant cells. 27 Using stable transgenic RNAi lines that knocked down BI-1 expression, Eichmann et al 28 concluded that the anti-cell death function of BI-1 benefits biotrophic B. graminis to penetrate into host plant cells by modulating the capacity of cell-wall-associated defense responses in barley. Recent reverse genetic studies using two T-DNA insertion mutants of AtBI-1 (atbi1-1 and atbi1-2) clearly demonstrated that these two loss-of-function mutants exhibited accelerated PCD phenotype upon treatment with a fungal toxin Fumonisin B1, when compared with wild-type plants.…”
Section: Bi-1 Is a Broad-spectrum Cell Death Suppressor In Plantsmentioning
confidence: 99%